HER3 targeting with an antibody‐drug conjugate bypasses resistance to anti‐HER2 therapies - Lucía Gandullo‐Sánchez; Emily Capone; Alberto Ocaña; Stefano Iacobelli; Gianluca Sala; Atanasio Pandiella (EMBO Molecular Medicine)
Abstract Despite impressive clinical benefit obtained with anti‐HER2‐targeted therapies, in advances stages, especially in the metastatic setting, HER2‐positive tumors remain incurable. Therefore, it is important to develop novel strategies to fight these tumors, especially when they become resistant to available therapies. We show here that the anti‐HER3 antibody–drug conjugate EV20/MMAF exerted potent anti‐tumoral properties against several models of primary resistance and secondary resistance to common anti‐HER2 available therapies, including trastuzumab, lapatinib, neratinib, and trastuzumab‐emtansine. HER3 was expressed in these HER2+ breast cancer cells and knockdown experiments demonstrated that HER3 expression was required for the action of EV20/MMAF. In mice injected with trastuzumab‐resistant HER2+ cells, a single dose of EV20/MMAF caused complete and long‐lasting tumor regression. Mechanistically, EV20/MMAF bound to cell surface HER3 and became internalized to the lysosomes. Treatment with EV20/MMAF caused cell cycle arrest in mitosis and promoted cell death through mitotic catastrophe. These findings encourage the clinical testing of EV20/MMAF for several indications in the HER2+ cancer clinic, including situations in which HER2+ tumors become refractory to approved anti‐HER2 therapies.